The Influence Of Motivation And Interest In Learning On The Learning Achievement Of XI Grade Students At SMK Perdana 1 Surabaya - Ambar Dwi Prastyo; Rifki Suwaji (SEAN Institute, 2024)
Abst Motivation and interest are two elements that are very influential in learning achievement. Students must have enthusiasm motivation and also interest in learning can be influential to achieve a desired achievement. High interest can facilitate effective learning. A quantitative approach was used in this study, using a non-probability methodology involving 40 students, to find the simultaneous and partial impact of the variables of motivation and interest in learning, on the variable of learning achievement at Smk Perdana 1 Surabaya. Data were obtained through questionnaires and processed using SPSS (Statistical Product And Service Solution) Version 26 software. In accordance with the results of the T test, the motivation variable has a positive and significant effect on learning achievement, with a value of 0.030 <0.05. The learning interest variable has a positive and insignificant effect on learning achievement, with a value of 0.268> 0.05. The F test shows that the learning achievement variable is jointly (simultaneously) influenced by the variables of motivation and interest in learning, while the coefficient of determination R Square shows that the conclusion from contribution of the motivation and interest in learning variables are 65.6%.